Academic Senate Minutes 2009-04-02 - Academic Senate:::::::::
Chair Report. Agenda approved. Minutes delayed. Philosophy curriculum changes approved. Philosophy pre-law concentration moved to business and postponed to next meeting. Special Report: Our EOP Academy – B. Peterson. New Concentration in ENSP approved. Revision to the Faculty Representation on Administrative Search Committees amended and approved. President's Report. Revision to the RTP policy approved. Vice President of SAEM Report. Statewide Senators Report. FSAC Report. Academic Affairs Strategic Plan - First Reading